2008
DOI: 10.1016/j.ajog.2007.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Intraabdominal pressure changes associated with lifting: implications for postoperative activity restrictions

Abstract: Objective-To describe the effect of lifting maneuver and quantity of weight lifted on the generation of intra-abdominal pressure.Study Design-Forty-one women undergoing urodynamic evaluation performed four lifting maneuvers, each while lifting 0, 2.5, 5, 10, and 15 kg. The lifting maneuvers were routine activities including squatting with and without assistance, lifting from a counter and receiving weight. Pressure was recorded with a rectal microtip catheter. Each lift was performed twice and the average pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Physical exertion increases the intraabdominal pressure and correspondingly the tensile forces distributed on the mesh reconstruction (34). While the universal recommendation to avoid lifting and carrying weights of >10 kg during the first 3 months appears to be adequate after open reconstruction, it may not be justified after laparoscopic surgery (35).…”
Section: Outcomes Of the Surgical Techniquesmentioning
confidence: 99%
“…Physical exertion increases the intraabdominal pressure and correspondingly the tensile forces distributed on the mesh reconstruction (34). While the universal recommendation to avoid lifting and carrying weights of >10 kg during the first 3 months appears to be adequate after open reconstruction, it may not be justified after laparoscopic surgery (35).…”
Section: Outcomes Of the Surgical Techniquesmentioning
confidence: 99%
“…Intra-abdominal pressures are reported from the literature for resting and pathological states, as well as for various activities (see Table 2). [1618] Laplace’s Law for thin-walled vessels considers wall tension as in Nout et al and assumes an abdominal radius of 0.15 m and an inter-stitch distance of 0.01m. [16] We estimated forces in each suture ranging from 2 N (resting normal state) to approximately 75 N for weight lifting.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that both hand-sewn and linear stapled closures had mean burst pressures significantly less than the maximal absolute intragastric pressures seen with normal daily activities [4][5][6][7], consistent with similar published reports [8][9][10]. Because both of these closures are highly dependable in clinical practice, absolute intralumenal pressure must not be the true maximal value a closure must be capable of withstanding, but rather the difference between the intralumenal and intraabdominal pressures, or the transmural pressure, which is significantly less.…”
Section: Dependabilitymentioning
confidence: 50%
“…3,4). When the stapler is fired, the mesh ring becomes affixed to the outer perimeter of the viscerotomy.…”
Section: Methodsmentioning
confidence: 99%